Thermosetting powder coating composition
By using carboxy functional polyesters composed of specific polyols and dicarboxylic acid residues, the problem of polyester reliance on aromatic monomers in existing powder coatings is solved, and improved mechanical properties and weatherability are achieved, especially performance improvements under light conditions.
Patent Information
- Application Number
- CN202380056520.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-27
- Filing Date
- 2023-07-26
- Publication Date
- 2025-04-08
AI Technical Summary
Typical polyesters in existing powder coatings rely on aromatic monomers to obtain glass transition temperature (Tg), limiting their weather resistance.
Using a carboxy functional polyester composed of 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol residues, powder coating compositions with improved mechanical properties and weather resistance were prepared by adjusting the stoichiometric amount of the polyol component and the dicarboxylic acid component.
It is achieved to improve the mechanical properties and weather resistance of the coating while maintaining the glass transition temperature suitable for the powder coating system, especially the gloss retention rate under xenon arc and UVB exposure.
Smart Images

Figure BDA0005257648010000121 
Figure BDA0005257648010000131 
Figure BDA0005257648010000141
Abstract
Description
Technical Field
[0001] The present invention relates to a powder coating composition comprising a carboxyl functional polyester. The polyester is composed of 2,2,4,4-tetramethyl-1,3-cyclobutanediol and 1,4-cyclohexanedimethanol residues. Background Art
[0002] Because powder coatings have good corrosion resistance and outdoor durability, the demand for powder coatings in the industry is increasing. There are many types of resin technologies that can be used for powder coatings. These resins include epoxy resins, polyesters, acrylic resins and mixtures thereof. For outdoor applications, polyesters, fluoropolymers and acrylic resins are generally used. Polyesters generally provide a good balance of desired coating properties (such as appearance and impact resistance), while acrylic resins and fluoropolymers generally show better weather resistance. The typical polyesters used in powder coatings rely on aromatic monomers to obtain an available glass transition temperature. This limits weather resistance. Therefore, it is very desirable to develop a powder coating having good weather resistance while also having a glass transition temperature (Tg) suitable for powder coating systems. g ) based polyester powder coating composition. Summary of the invention
[0003] In general, the present invention provides polyester-based powder coating compositions for coating formed or shaped articles, the polyester-based powder coating compositions exhibiting improved mechanical properties and weathering resistance. Generally speaking, the polyester is composed of about 25 mol % to about 75 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol (TMCD) residues and about 20 mol % to about 65 mol % of 1,4-cyclohexanedimethanol residues. The polyester component of the composition is primarily formulated in a carboxyl-functional form and has an acid value of about 20 mg KOH / g resin to 100 mg KOH / g resin, and is therefore suitable for crosslinking with crosslinking compounds known to react with such carboxyl groups in a thermosetting powder coating composition system. Exemplary crosslinking agents include β-hydroxyalkylamides and glycidyl-functional compounds. BRIEF DESCRIPTION OF THE DRAWINGS
[0004] Figure 1 Xenon arc weathering of black coatings obtained according to ISO test 16474-2 is described, comparing TMCD-based resins to fluoroethylene vinyl ether-based resins and superdurable control resins. These coating compositions were formulated without the addition of light stabilizers. In this figure, 60 degree gloss retention is plotted versus hours. The circular data points represent the coating of Example 21, the triangular data points represent Example 17, and the diamond data points represent Example 19.
[0005] Figure 2Depicted is the Xenon Arc Weathering of black coatings obtained according to ISO Test 16474-2, comparing TMCD based resins to fluoroethylene vinyl ether based resins and an ultradurable control resin. These coating compositions were formulated with the addition of a light stabilizer. In this figure, 60 degree gloss retention is plotted versus hours. The circular data points represent the coating of Example 20, the triangular data points represent Example 16, and the diamond data points represent Example 18.
[0006] Figure 3 UV 313 nm bulb weatherability of black coatings obtained according to ISO test 16474-3 is described, comparing TMCD-based resins to fluoroethylene vinyl ether-based resins and superdurable control resins. These coating compositions were formulated without the addition of light stabilizers. In this figure, 60 degree gloss retention is plotted versus hours. The circular data points represent the coating of Example 21, the triangular data points represent Example 17, and the diamond data points represent Example 19.
[0007] Figure 4 UV 313 nm bulb weatherability of black coatings obtained according to ISO test 16474-3 is described, comparing TMCD-based resins to fluoroethylene vinyl ether-based resins and superdurable control resins. These coating compositions were formulated with the addition of light stabilizers. In this figure, 60 degree gloss retention is plotted versus hours. The circular data points represent the coating of Example 20, the triangular data points represent Example 16, and the diamond data points represent Example 18. DETAILED DESCRIPTION
[0008] In a first aspect, the present invention provides a powder coating composition comprising:
[0009] A. at least one carboxyl-functional polyester comprising:
[0010] 1. A polyol component comprising:
[0011] i. about 25 mol % to about 75 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues based on the total moles of i., ii., iii., and iv.;
[0012] ii. about 20 mol % to about 65 mol % of 1,4-cyclohexanedimethanol residues based on the total moles of i., ii., iii., and iv.;
[0013] iii. 0 mol % to about 15 mol % of acyclic diol residues based on the total moles of i., ii., iii., and iv.; and
[0014] iv. about 3 mol % to about 20 mol % of trimethylolpropane residues, based on the total moles of i., ii., iii., and iv.; and
[0015] 2. A dicarboxylic acid component comprising:
[0016] v. from about 70 mol % to about 100 mol % of hexahydrophthalic anhydride residues, based on the total moles of v. and vi.; and
[0017] vi. 0 mol % to about 30 mol % of acyclic diacid residues based on the total moles of v. and vi.;
[0018] wherein the polyester has a glass transition temperature of about 45°C to 90°C, an acid value of about 20 mg KOH / g to about 100 mg KOH / g, a number average molecular weight of about 2,000 g / mol to 10,000 g / mol, and a weight average molecular weight of about 5,000 g / mol to 100,000 g / mol; and
[0019] B. One or more compounds reactive with the carboxyl functional polyester.
[0020] It should be understood that the following is not intended to be an exhaustive list of defined terms. Other definitions may also be provided in the specification, for example, when the defined terms are used in context. As used herein, the terms "one", "an" and "the" represent one or more. As used herein, the term "and / or" when used in a list of two or more items means that any one of the listed items can be used alone, or any combination of two or more of the listed items can be used. For example, if a composition is described as containing components A, B and / or C, then the composition may contain only A; only B; only C; a combination of A and B; a combination of A and C, a combination of B and C; or a combination of A, B and C.
[0021] As used herein, the term "polyester" is intended to include "copolyesters" and should be understood to mean a synthetic polymer prepared by the reaction of one or more difunctional carboxylic acids and / or polyfunctional carboxylic acids with one or more difunctional hydroxy compounds and / or polyfunctional hydroxy compounds, as described above as consisting of a dicarboxylic acid component and a polyol component. Typically, the difunctional carboxylic acid can be a dicarboxylic acid, and the difunctional hydroxy compound can be a dihydric alcohol (dihydric alcohol), such as a diol (glycols) and a diol (diols). As used herein, the term "polyol" includes but is not limited to diols, diols and / or polyfunctional hydroxy compounds. As used herein, the term "residue" means any organic structure incorporated into a polymer by polycondensation and / or esterification of the corresponding monomers. As used herein, the term "repeat unit" means an organic structure having a dicarboxylic acid residue and a diol residue bonded by an ester group. Thus, for example, a dicarboxylic acid residue can be derived from a dicarboxylic acid monomer or its associated acyl halide, ester, salt, anhydride and / or mixtures thereof. In addition, as used herein, the term "diacid" includes polyfunctional acids. Thus, as used herein, the term "dicarboxylic acid" is intended to include dicarboxylic acids and any derivatives of dicarboxylic acids, including their associated halides, esters, half-esters, salts, half-salts, anhydrides, mixed anhydrides and / or mixtures thereof, that can be used in the reaction process with the diols to prepare the polyesters.
[0022] The stoichiometry of the polyol component and the dicarboxylic acid component may be adjusted as necessary to obtain the desired acid value (and / or hydroxyl number) in the final carboxyl-functional polyester used in the powder coating composition.
[0023] The polyester portion of the composition of the present invention can be prepared by methods known in the art, for example, by methods in homogeneous solutions, by transesterification methods in melts, and by two-phase interface methods. Suitable methods include, but are not limited to, reacting one or more dicarboxylic acids with one or more diols at a temperature of 100° C. to 315° C. and a pressure of 0.1 mmHg to 760 mmHg for a time sufficient to form polyesters. For methods of producing polyesters, see U.S. Pat. No. 3,772,405, the disclosure of which is hereby incorporated by reference herein.
[0024] In one embodiment, the carboxyl functional polyester consists entirely of aliphatic groups or consists essentially of no aromatic groups. In another embodiment, the carboxyl functional polyester contains no more than about 10 mole % of aromatic diacid residues, such as isophthalic acid and terephthalic acid, based on the total moles of dicarboxylic acid components.
[0025] In another embodiment, the polyol component comprises from about 30 mol % to about 65 mol %, from about 35 mol % to about 65 mol %, or from about 25 mol % to about 55 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues; from about 30 mol % to about 60 mol % or from about 40 mol % to about 60 mol % of 1,4-cyclohexanedimethanol residues; 0 mol % to about 10 mol % of acyclic diols, and from about 3 mol % to about 20 mol %, from about 3 mol % to about 15 mol %, or from about 5 mol % to 15 mol % of trimethylolpropane residues; and the dicarboxylic acid component comprises from about 100 mol % to about 80 mol % of hexahydrophthalic anhydride residues; and 0 mol % to about 20 mol % of acyclic diacid residues.
[0026] In another embodiment, the polyol component comprises from about 40 mole % to about 55 mole % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, from about 40 mole % to 55 mole % of 1,4-cyclohexanedimethanol residues, from 0 mole % to about 5 mole % of a non-cyclic diol, and from 3 mole % to about 15 mole % or from about 5 mole % to about 15 mole % of trimethylolpropane residues, and wherein the dicarboxylic acid component comprises from about 90 mole % to about 100 mole % of hexahydrophthalic anhydride residues, and from 0 mole % to about 10 mole % of a non-cyclic aliphatic diacid.
[0027] Exemplary non-cyclic diols include neopentyl glycol (NPG), 2-butyl-2-ethyl-1,3-propanediol (BEPD), hydroxypivaloyl hydroxypivalate (HPHP), 1,6-hexanediol, 1,4-butanediol, ethylene glycol, propylene glycol, 2-methyl-1,3-propanediol (MPDiol), and mixtures thereof. In one embodiment, the non-cyclic diol is neopentyl glycol, i.e., 2,2-dimethylpropane-1,3-diol.
[0028] In certain embodiments, the non-cyclic diacid is a C4-C 10 Diacids. Exemplary non-cyclic diacids include succinic acid, adipic acid, and sebacic acid. In one embodiment, the non-cyclic diacid is adipic acid.
[0029] As described above, in one aspect, the carboxyl functional polyester has an acid value of about 20 mg KOH / g resin to about 100 mg KOH / g resin. In certain embodiments, the polyester has an acid value of about 30 mg KOH / g to about 80 mg KOH / g, about 35 mg KOH / g to about 70 mg KOH / g, or about 40 mg KOH / g to about 60 mg KOH / g.
[0030] In certain embodiments, the carboxyl functional polyester has a hydroxyl number of 0 mg KOH / g resin to about 20 mg KOH / g resin, 0 mg KOH / g resin to about 15 mg KOH / g resin, 0 mg KOH / g resin to about 10 mg KOH / g resin, or 0 mg KOH / g resin to about 5 mg KOH / g resin.
[0031] As described above, the carboxyl functional polyester has a glass transition temperature of about 45°C to 90°C. In certain embodiments, the polyester has a T of about 50°C to 80°C, 50°C to 70°C, or about 55°C to about 75°C. g .
[0032] As described above, the carboxyl functional polyester will have a number average molecular weight of about 2,000 g / mol to about 10,000 g / mol. In certain embodiments, the carboxyl functional polyester will have a number average molecular weight of about 2,000 g / mol to about 9,000 g / mol or about 2,000 g / mol to about 8,000 g / mol. As described above, the carboxyl functional polyester will have a weight average molecular weight of about 5,000 to about 100,000. In certain embodiments, the carboxyl functional polyester will have a weight average molecular weight of about 5,000 g / mol to about 80,000 g / mol or about 5,000 g / mol to about 50,000 g / mol.
[0033] In certain embodiments, the compound that reacts with the carboxyl functional polyester is a crosslinking agent selected from β-hydroxyalkylamides and glycidyl functional compounds. In certain embodiments, the β-hydroxyalkylamide is selected from bis(N,N'-dihydroxyethyl)adipamide, bis(N,N'-dihydroxypropyl)adipamide, or mixtures thereof. Commercially available β-hydroxyalkylamides include bis(N,N'-dihydroxyethyl)adipamide ( XL-552), bis(N,N'-dihydroxypropyl) adipamide( QM-1260) and SF-4510. Megamid XL is also commercially available from MEGARA RESINS-ANASTASIOS FANIS SA.
[0034] Commercially available glycidyl functional curing agents include the glycidyl-based crosslinkers available from Huntsman as Araldite PT 810, PT 910, and PT 912. Glycidyl acrylates and glycidyl methacrylates, such as those commercially available from Estron Chemical as GMA 300G, 400G, and 500, are also suitable.
[0035] In other embodiments, the compound that reacts with the carboxyl functional polyester is an epoxy resin. Exemplary epoxy resins include those having a molecular weight of about 300 to about 4000 and having about 0.05 to about 0.99 epoxy groups per 100 grams of resin (i.e., 100-2000 weight per epoxide (WPE)). Such resins are widely known and can be Trademark (Hexion) and Commercially available from Huntsman.
[0036] In the coating composition of the present invention, in certain embodiments, the polyester is present in an amount of about 70% to about 97% by weight based on the total amount of the carboxyl functional polyester and the crosslinker, and the crosslinker is present in an amount of about 3% to about 30% by weight based on the total amount of the carboxyl functional polyester and the crosslinker. In another embodiment, in the coating composition of the present invention, the carboxyl functional polyester is present in an amount of about 75% to 95% by weight or 80% to 90% by weight based on the total weight of the carboxyl functional polyester and the crosslinker, and the crosslinker is present in an amount of about 5% to 25% by weight or 10% to 20% by weight based on the total weight of the carboxyl functional polyester and the crosslinker.
[0037] In another aspect, the present invention provides a powder coating composition comprising:
[0038] A. at least one carboxyl-functional polyester comprising:
[0039] 1. A polyol component comprising:
[0040] i. about 40 mol % to about 55 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues based on the total moles of i., ii., iii., and iv.;
[0041] ii. about 40 mol % to about 55 mol % of 1,4-cyclohexanedimethanol residues based on the total moles of i., ii., iii., and iv.;
[0042] iii. 0 mol % to about 5 mol % of acyclic diol residues based on the total moles of i., ii., iii., and iv.;
[0043] iv. about 5 mol % to about 12 mol % of trimethylolpropane residues, based on the total moles of i., ii., iii., and iv.; and
[0044] 2. A dicarboxylic acid component comprising:
[0045] v. about 90 mol % to about 100 mol % of hexahydrophthalic anhydride residues, based on the total moles of v. and vi.; and
[0046] vi. 0 mol % to about 10 mol % of acyclic diacid residues based on the total moles of v. and vi.;
[0047] wherein the polyester has a glass transition temperature of about 45°C to 90°C, an acid value of about 20 mg KOH / g to about 80 mg KOH / g, a number average molecular weight of about 2,000 g / mol to 10,000 g / mol, and a weight average molecular weight of about 5,000 g / mol to 100,000 g / mol; and
[0048] B. β-Hydroxyalkylamide crosslinking agent.
[0049] In one embodiment, the beta-hydroxyalkylamide crosslinker will be present in an amount from about 3 wt% to about 20 wt% based on the total weight of A and B.
[0050] In other embodiments, the powder coating composition of the present invention may also include waxes, pigments, fillers, degassing agents, flow agents and / or other additives. Examples of pigments include inorganic pigments and organic pigments, such as titanium dioxide, iron oxide, chromium oxide, zinc sulfide, zinc phosphate, mica, azo compounds, etc. Suitable fillers include silicates, sulfates and carbonates. Examples of additives include degassing agents, antioxidants and UV stabilizers. Exemplary weathering stabilizers that can be used in these embodiments include hindered amine light stabilizers and UV absorbers. Examples of degassing agents include cyclohexanedimethanol dibenzoate, benzoin and benzoin derivatives. Examples of flow control agents include 361N(BYK) and PV-5 (Estron). Other examples of typical additives for powder coating compositions can be found in US Pat. No. 10,916,539, which is incorporated herein by reference.
[0051] The powder coating composition of the present invention can be prepared by any method known in the art. In a typical method, a powder of a carboxyl functional polyester and a crosslinking agent is mixed with any desired additives at room temperature to obtain a premix. The premix is then extruded at an elevated temperature, e.g., 80° C. to 130° C., 90° C. to 125° C., or 100° C. to 120° C., to produce an extrudate, which is then cooled to solidify the mixture. The resulting solid is then ground into a powder, which is then sieved to classify according to the particle size of the particles. The powder coating of the present invention preferably has a particle size of less than about 120 μm, less than 110 μm, or less than 100 μm.
[0052] The powder coating composition can be applied to the substrate by common methods such as electrostatic spray deposition (ESD) or fluidized bed application. The coating can be cured at 140°C to 220°C, 140°C to 200°C, 140°C to 180°C, or 140°C to 160°C for 10 minutes to one hour, or under other suitable conditions.
[0053] See also: User's Guide to Powder Coating, 4th Edition, Nicholas Liberto, ed., Society of Manufacturing Engineers (2003).
[0054] As described above, the powder coating composition of the present invention can be applied to a substrate or a molded or formed article. Therefore, another aspect of the present invention is a molded or formed article, at least a portion of which has been coated with the coating composition of the present invention. The substrate can be any common substrate, such as aluminum, tin, steel or galvanized sheet, etc. The coating composition can be applied to the substrate with a thickness of about 1 mil to about 10 mils (1 mil = 25 μm) using techniques known in the art (e.g., by electrostatic spray deposition (ESD) or fluidized bed application). The coating can be cured at a temperature of about 140°C to about 230°C for a period of about 10 minutes to about 60 minutes, and the coating is allowed to cool.
[0055] One mechanical property of the cured (i.e., thermosetting) powder coatings of the present invention can be determined by the Erichsen cupping test according to ISO- 1520. In some embodiments, the powder coatings of the present invention exhibit an Erichsen cupping test rating for cracking greater than 4.0 mm, greater than 4.5 mm, or greater than 5 mm.
[0056] The weatherability of the powder coatings of the present invention can be determined by the rate of gloss loss over time under xenon arc, UVA or UVB exposure. The superior weatherability of the present invention is demonstrated by comparing its performance to fluoroethylene vinyl ether (FEVE) such as those sold under the trademark Lumiflon TM The common test methods specified by the global quality label organization QUALICOAT for these comparisons are Xenon Arc according to ISO 16474-2 and UVB according to ISO 16474-3.
[0057] Thus, in certain embodiments, the cured coating compositions on such articles exhibit improved performance characteristics. For example, according to ISO-1520, articles coated with the cured compositions of the present invention may exhibit an Erickson cupping test rating of greater than 4.0 mm for crack generation. Additionally or separately, according to ISO 16474-3, at 5,000 hours of UVB exposure, the cured coating composition may exhibit a 60-degree gloss retention weatherability of greater than 45% or greater than 50%, and according to ISO 16474-2, at 7,000 hours of xenon arc exposure, the cured coating composition may exhibit a 60-degree gloss retention weatherability of 50%.
[0058] The present invention can be further illustrated by the following examples of certain embodiments, but it should be understood that these examples are included for illustrative purposes only and are not intended to limit the scope of the present invention unless otherwise explicitly stated.
[0059] Example
[0060] In these examples, the following abbreviations are used:
[0061] TMCD = 2,2,4,4-tetramethyl-1,3-cyclobutanediol, purchased from Eastman Chemical Company
[0062] TMP = trimethylolpropane, purchased from Sigma-Aldrich
[0063] CHDM = 1,4-cyclohexanedimethanol, available from Eastman Chemical Company
[0064] Benzoin = degassing agent, purchased from Estron Inc.
[0065] HHPA = hexahydrophthalic anhydride, purchased from Sigma-Aldrich
[0066] TPP = triphenyl phosphite, purchased from Sigma-Aldrich
[0067] IPA = purified isophthalic acid, purchased from Sigma-Aldrich
[0068] P EPQ= P- Powdered antioxidant, purchased from Clariant
[0069] XL 552-hydroxyalkylamide crosslinker, purchased from Estron inc.
[0070] Vestagon P1540-urethane crosslinker, purchased from Evonik
[0071] GMA 300 - Glycidyl acrylate crosslinker, purchased from Estron Inc.
[0072] PL-200 - Flow and wetting additive, available from Estron Inc.
[0073] Butaflow BT-71-curing catalyst, purchased from Estron Inc
[0074] 1076-Antioxidant, purchased from BASF
[0075] XF-barium sulfate pigment, purchased from Cimbar Inc.
[0076] M130-red iron oxide, purchased from Lanxess
[0077] Black 10P922 - Iron oxide pigment, purchased from Shepherd Inc.
[0078] YL 196 - yellow inorganic pigment, purchased from Shephard Inc
[0079] Ti Pure TM TS 6200 - Titanium dioxide, purchased from Chemours Inc.
[0080] Ravenblack 5000UII, purchased from Brila Inc
[0081] 405 is a UV absorber purchased from BASF
[0082] 144 is a hindered amine light stabilizer purchased from BASF
[0083] A set of resins was prepared to determine the effect of resin properties and composition on mechanical properties. TMCD levels, TMP (trimethylolpropane) levels, and acid values were varied. Table 1 shows the molar composition of the diols / polyols used in the experiments. Example 4 is a comparative example that contains an aromatic diacid, i.e., isophthalic acid (IPA).
[0084] Table 1
[0085]
[0086] Table 2 - Weight Percentage of Monomer Feed Resins
[0087] Example No. HHPA IPA TMCD CHDM TMP 1 57.5 -- 19.6 20.5 2.4 2 58 -- 11 27 3.9 3 57.8 -- 19.5 19.5 3.2 4 (Comparison) 29.3 28.3 11.1 27.3 4
[0088] Note: Triphenyl phosphite and 4100 catalyst (PMC) accounted for 0.1% of the total feed weight.
[0089] Typical synthesis procedure :
[0090] The polymerization reaction was controlled using the Camille procedure. The resin was prepared in a two-liter reaction kettle equipped with a heating mantle, a mechanical stirrer, a thermocouple, a nitrogen blanket, an oil-heated partial condenser (103°C-105°C), a condensation trap, and a water-cooled total condenser (15°C). Unless otherwise stated, the entire reaction was carried out under a nitrogen blanket (0.4 standard cubic centimeters per minute or sccm). The reaction procedure was as follows:
[0091] A: The first-stage monomers (hexahydrophthalic anhydride, TMP, and 2,2,4,4-tetramethyl-1,3-cyclobutanediol) were added to the reactor, the reaction solution was heated to 100° C. under a nitrogen blanket to allow the mixture to begin to melt, and stirring was started at 100° C. The stirring speed of the reaction was set to 300 rpm and increased until the reaction was completed.
[0092] B: As exotherm occurred, the temperature jumped to 165°C at 1°C / min. After the exotherm ceased, the reaction was cooled to 150°C.
[0093] C: Add the second stage monomers (neopentyl glycol and / or CHDM) and antioxidant (triphenyl phosphite) to the reaction mixture at 150°C. The temperature of the reaction is increased to 235°C at 0.1°C / minute. The reaction is maintained at 235°C until the desired acid value is reached. The nitrogen blanket flow rate is increased to 1.0 sccm, and the nitrogen subsurface flow rate is started at 1.0 sccm. When the acid value is about 5 mg KOH / g away from the target acid value, the stirring speed is increased to 350 rpm to 400 rpm to drive the reaction to the desired acid value. Samples are taken every hour (stirring is stopped when sampling) to monitor the acid value and viscosity of the entire reaction.
[0094] D: After the desired acid value was reached, the reaction mass was poured into a large baking pan (turkey pan). The resin mass was allowed to cool and was broken into small pieces for further grinding. The ground resin was tested to determine properties such as acid value, hydroxyl number, melt viscosity, molecular weight, monomer composition by gas chromatography (GC), glass transition temperature by DSC, and color. The final resin composition properties are shown in Table 3
[0095] Table 3
[0096] Resin Example No. <![CDATA[T g (℃)]]> Acid value Hydroxyl number <![CDATA[M n (g / mol)]]> Mw(g / mol) 1 63.99 36.3 6.5 3,546 12,375 2 58.4 34.1 6.8 4,176 31,108 3 53 33.2 4.3 3,196 11,391 4 (Comparison) 63.05 35 14.6 4,918 240,078
[0097] Coating Composition Examples (in grams) - Table 4
[0098]
[0099]
[0100] Each coating composition was weighed into a container. The composition was then milled using a Vitamix mill. The resulting milled composition was extruded on a dual-zone twin-screw extruder at 320 RPM and 60%-70% torque. Zone 1 was heated to 100°C, while the temperature of Zone 2 was 110°C. The composition was cooled on a double-roll cooler at 2°C to 5°C and collected in a plastic bag. The composition was completely cooled to room temperature overnight. They were then ground into powder using a Strand mill. The resulting powder coating composition was sieved with a 106 micron screen. The sieved composition can be sprayed immediately.
[0101] The coating composition was applied to AQT 36 aluminum from Q-panel using an electrostatic spray gun. The coated panels were placed in an electric oven and cured at 200° C. for a total of 20 minutes. The resulting coating had a cured film specification of 2 mils to 2.5 mils.
[0102] The flexibility of the coating was tested using the Erickson cupping test specified in the Qualicoat Class 3 specification (using ISO 1520). The results are listed in Table 5 below:
[0103] Table 5
[0104]
[0105] As shown in the results, using TMCD, a Tg greater than 50°C and good Erichsen cupping can be achieved without the use of an aromatic component in the resin.
[0106] Weathering Example
[0107] TMCD resins were prepared and tested in the Xenon 16474-2 and UVB 16474-3 accelerated weathering tests. The resin tested was Resin Example 3, but formulated to an acid number of 31.8, but otherwise prepared as described above. Two control resins were also tested. A commercially available superdurable resin (SDP Crylcoat 4659) known to be composed of aromatic diacid residues and having a Tg of 59°C, and a commercial fluoroethylene vinyl ether (FEVE) resin Lumiflon 710. The coating compositions are shown in Table 6 below (in grams).
[0108] Table 6
[0109]
[0110]
[0111] Each coating composition was weighed into a container. The composition was then milled using a Vitamix mill. The resulting milled composition was extruded on a dual-zone twin-screw extruder at 320 RPM and 60%-70% torque. Zone 1 was heated to 100°C, while the temperature of Zone 2 was 110°C. The coating composition was cooled on a double-roll cooler at 2°C to 5°C and collected in a plastic bag. The composition was completely cooled to room temperature overnight. They were then ground into powder using a Strand mill. The resulting composition was sieved with a 106 micron screen. The sieved powder coating composition can be sprayed immediately.
[0112] The composition was applied to AQT 36 aluminum from Q-panel using an electrostatic spray gun. The coated panels were placed in an electric oven and cured at 200°C for a total of 20 minutes. The coated panels were repeatedly placed in a weathering test chamber operating at ISO 16474-2 (Xenon Arc) and ISO 16474-3 (UVB).
[0113] like Figures 1 to 4 As shown, the accelerated weathering data clearly demonstrates that the performance of TMCD-based resins is comparable to that of fluoroethylene vinyl ether (FEVE)-based resins.
Claims
1. A powder coating composition comprising: A. at least one carboxyl-functional polyester comprising:
1. A polyol component comprising: i. about 25 mol % to about 75 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues based on the total moles of i, ii, iii, and iv; ii. about 20 mol % to about 65 mol % of 1,4-cyclohexanedimethanol residues based on the total moles of i, ii, iii and iv; iii. 0 mol % to about 15 mol % of acyclic diol residues based on the total moles of i, ii, iii and iv; and iv. about 3 mol % to about 20 mol % of trimethylolpropane residues based on the total moles of i, ii, iii and iv; and 2. A dicarboxylic acid component comprising: v. from about 70 mol % to about 100 mol % of hexahydrophthalic anhydride residues, based on the total moles of v and vi; and vi. 0 mol % to about 30 mol % of acyclic diacid residues, based on the total moles of v and vi; wherein the polyester has a glass transition temperature of about 45°C to 90°C, an acid value of about 20 mg KOH / g to about 100 mg KOH / g, a number average molecular weight of about 2,000 g / mol to 10,000 g / mol, and a weight average molecular weight of about 5,000 g / mol to 100,000 g / mol; and B. One or more compounds reactive with the carboxyl functional polyester.
2. The composition of claim 1 wherein the compound reactive with the carboxyl functional polyester is a crosslinking agent selected from the group consisting of beta-hydroxyalkylamides and glycidyl functional compounds.
3. The composition of claim 1 wherein the compound reactive with the carboxyl functional polyester is an epoxy resin.
4. The composition of claim 1, wherein the polyol component comprises from about 30 mol % to about 65 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues; from about 30 mol % to about 60 mol % of 1,4-cyclohexanedimethanol residues; 0 mol % to about 10 mol % of acyclic diols, and wherein the dicarboxylic acid component comprises from about 100 mol % to about 80 mol % of hexahydrophthalic anhydride residues; and 0 mol % to about 20 mol % of acyclic diacid residues.
5. The composition of claim 1, wherein the polyol component comprises from about 40 mol % to about 55 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues, from about 40 mol % to 55 mol % of 1,4-cyclohexanedimethanol residues, from 0 mol % to about 5 mol % of acyclic diols, and from 3 mol % to about 15 mol % of trimethylolpropane residues, and wherein the dicarboxylic acid component comprises from about 90 mol % to about 100 mol % of hexahydrophthalic anhydride residues, and from 0 mol % to about 10 mol % of acyclic aliphatic diacids.
6. The composition of claim 1, wherein the acyclic diol is selected from the group consisting of neopentyl glycol, 1,6-hexanediol, 1,4-butanediol, 2-methyl-1,3-propanediol, and 2-butyl-2-ethyl-1,3-propanediol.
7. The composition of claim 1, wherein the acyclic diol is neopentyl glycol.
8. The composition of claim 1, wherein the non-cyclic diacid is selected from succinic acid, adipic acid, and sebacic acid.
9. The composition of claim 1, wherein the non-cyclic diacid is adipic acid.
10. The composition of claim 1, wherein the polyester has an acid value of about 40 mg KOH / g to 60 mg KOH / g.
11. The composition of claim 1, wherein the polyester has a T of about 55°C to about 75°C. g .
12. The composition according to claim 1, wherein the β-hydroxyalkylamide is selected from bis(N,N'-dihydroxyethyl)adipamide, bis(N,N'-dihydroxypropyl)adipamide, or a mixture thereof.
13. The coating composition of claim 1, wherein the polyester is present in an amount of about 70 wt % to about 97 wt % based on the total amount of the polyester and the crosslinker, and the crosslinker is present in an amount of about 3 wt % to about 30 wt % based on the total amount of the polyester and the crosslinker.
14. A powder coating composition comprising: A. at least one carboxyl-functional polyester comprising:
1. A polyol component comprising: i. about 40 mol % to about 55 mol % of 2,2,4,4-tetramethyl-1,3-cyclobutanediol residues based on the total moles of i., ii., iii., and iv.; ii. about 40 mol % to about 55 mol % of 1,4-cyclohexanedimethanol residues based on the total moles of i., ii., iii., and iv.; iii. 0 mol % to about 5 mol % of acyclic diol residues based on the total moles of i., ii., iii., and iv.; iv. about 5 mol % to about 12 mol % of trimethylolpropane residues, based on the total moles of i., ii., iii., and iv.; and 2. A dicarboxylic acid component comprising: v. about 90 mol % to about 100 mol % of hexahydrophthalic anhydride residues, based on the total moles of v. and i.; and vi. 0 mol % to about 10 mol % of acyclic diacid residues based on the total moles of v. and vi.; wherein the polyester has a glass transition temperature of about 45°C to 90°C, an acid value of about 20 mg KOH / g to about 80 mg KOH / g, a number average molecular weight of about 2,000 g / mol to 10,000 g / mol, and a weight average molecular weight of about 5,000 g / mol to 100,000 g / mol; and B. β-Hydroxyalkylamide crosslinking agent.
15. The composition of claim 14, wherein the β-hydroxyalkylamide crosslinker is present in an amount of about 3 wt% to about 20 wt% based on the total weight of A and B.
16. An article coated with the cured coating composition of claim 1 or claim 14.
17. The article of claim 16, wherein the cured coating exhibits an Erichsen Cupping Delamination Test rating for crack initiation greater than 4.5 mm according to ISO-1520.
18. The article of claim 16, wherein the cured coating exhibits a 60 degree gloss retention weatherability of greater than 45% at 5,000 hours of UVB exposure according to ISO 16474-3 and a 60 degree gloss retention weatherability of greater than 50% at 7,000 hours of Xenon arc exposure according to ISO 16474-2.
Citation Information
Patent Citations
Semiconductor device having a transistor portion that includes an output resistive portion
US10916539B2
Process for preparing aromatic diester containing copolyesters and products obtained thereby
US3772405A